PENGARUH PENGENDALIAN INTERNAL, KESESUAIAN KOMPENSASI DAN KETAATAN ATURAN TERHADAP KECURANGAN AKUNTANSI (Studi Pada Pemerintah Kota Lhokseumawe) - Sulaiman Sulaiman; Zulkarnaini Zulkarnaini (Jurnal Akuntansi dan Pembangunan (JAKTABANGUN) STIE Lhokseumawe, 2016)
This research aims to identify and analyze the effect of internal control and suitability of reward and compliance to accounting rules to the level trends of accounting fraud in the City of Lhokseumawe. Primary data were collected using a survey of civil servants (PNS) that work on the financial section in 3 Units (SKPD) Lhokseumawe Government. The sampling technique used is purposive sampling. Data analysis in this study using multiple linear regression analysis. The results of this research indicate that the internal control and suitability of reward and compliance to accounting rules partially negative and significant impact on the trend of fraud in the City of Lhokseumawe. Values obtained from this research Adjusted R Square of 093, this figure shows that the trend of Accounting fraud in Lhokseumawe Government influenced by internal control and compensation amounted to 27.9%, while 93% is influenced by other factors outside the two independent variables in this research.